البنيات الأسلوبية في رواية الشوك والقرنفل ليحي السنوار - رشيدة خلفاوي; صابرين دحدي (University of Eloued جامعة الوادي, 2025)
الملخص: لقد تطرقنا في بجثنا هذا إلى دراسة الأسلوبية من حيث الجانب النظري " ماهية الأسلوبية والأسلوب و الاتجاهات الأسلوبية ومحددات الأسلوب " والجانب التطبيقي درسنا فيه آليات التحليل الأسلوبي والتي هي محددات الأسلوب ومستويات التحليل الأسلوبي والانزياحات" - هذه الدراسة كانت جديدة في مجال الأسلوبية وخاصة من حيث أسلوب الكاتب وكشف لنا جميع مميزات هذا الأسلوب من واقعية الاختيار لبعض القضايا الجديدة التي تخص الأرض المحتلة فلسطين والتي سردها في رواية الشوك والقرنفل والتي قمنا نحن بتحليلها أسلوبيا . Abstract In this paper, we have touched upon the study of Stylistics in terms of the theoretical aspect "what is Stylistics, style, stylistic trends and style determinants" and the applied aspect, in which we studied the mechanisms of stylistic analysis, which are the determinants of style, levels of stylistic analysis and offsets" - This study was new in the field of Stylistics, especially in terms of the writer's style, and revealed to us all the features of this method from the realism of the choice of some new issues related to the occupied land of Palestine, which he recounted in the novel thorns and cloves, which we analyzed stylistically .
مذكرة .ماستر . لسانيات عامة. 2025
Keywords: الأسلوبية – التحليل الأسلوبي – يحي السنوار – رواشة الشوك والقرنفل